2017
DOI: 10.9734/arrb/2017/34318
|View full text |Cite
|
Sign up to set email alerts
|

P53 Expression in Response to Equigan Induced Testicular Injury and Oxidative Stress in Male Rat and the Possible Prophylactic Effect of Star Anise Extracts

Abstract: Objectives:Equigan is an anabolic androgenic steroid that developed for veterinary use to improve the food producing animal growth rate through promoting protein synthesis and muscle growth. The current study aimed to investigate the possible prophylactic effect of star anise extracts (SAE) response of to Equigan induced testicular injury, oxidative stress, P53 expression in male rats. Materials and Methods: Forty adult male rats were equally divided into four groups. 1 st Control El-Masry et al.; ARRB, 14(1):… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…These results agree with Pitts and Davis (2007) who reported that an evidence-based analysis of anabolic steroids also enhances performance in horses. Also, the current results agree with Barakat et al (2015) and El-Masry et al (2017).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results agree with Pitts and Davis (2007) who reported that an evidence-based analysis of anabolic steroids also enhances performance in horses. Also, the current results agree with Barakat et al (2015) and El-Masry et al (2017).…”
Section: Discussionsupporting
confidence: 93%
“…Anabolic-androgenic steroids are defined as synthetic derivatives of the endogenous sex hormone testosterone that plays a key role in the development of male reproductive tissue (such as the testis and prostate) as well as in puberty, sexual behavior, spermatogenesis and plays promoting secondary sexual characteristics such as increased muscle, bone mass and hair growth (Mitchell et al, 2009;Balthazart, Ball, 2010;Mohammed et al, 2016). Anabolic steroids are forbidden for meat production and human use in KAS, and most countries worldwide due to their undesirable effects included blood and cardiovascular disorders (Santos et al, 2006;Tousson et al, 2016;Waljee et al, 2016), liver dysfunction (Van Amsterdam et al, 2010;Barakat et al, 2015), kidney disease (Barakat et al, 2015), tendon damage (Battista, Combs, Warne, 2003), testicular problems (Tousson et al, 2012;El-Masry et al, 2017), psychiatric and behavioural disorders in both sexes (Salas-Ramirez, Montalto, Sisk, 2010), as well as other problems on the human body (Saleh, Waded, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…An efficient and competitive ACE-I, captopril is capable of reducing Ang II synthesis by acting as an antagonist to enzyme-converting angiotensin in plasma, tissue, and atherosclerotic plaque, as well as diminishing water-sodium retention, disrupting bradykinin breakdown, and regulating blood pressure by suppressing the production of aldosterone and thus inducing the dilation of the coronary and peripheral arteries [60,61]. When there is a lack of equilibrium between the ROS and antioxidant levels, the "redox" status of cells becomes imbalanced, which gives rise to oxidative stress [62,63]. In the external environment, ROS occur in pollutants, tobacco smoke, and radiation.…”
mentioning
confidence: 99%
“…Serum urea and creatinine were determined in the rat sera according to Oyouni et al [17] and Eldaim et al [18] respectively. The approach proposed by El-Masry et al [19] was followed to measure the levels of serum electrolytes (Potassium, sodium, calcium and chloride ion) using commercial kits (Sensa core electrolyte, India) according to El-Masry et al [19] or Tousson et al [20].…”
Section: Electrolytes and Kidney Functions Biomarkersmentioning
confidence: 99%